Echocardiographic prevalence of rheumatic heart disease in Indian school children using World Heart Federation criteria – A multi site extension of RHEUMATIC study (the e-RHEUMATIC study). (15th December 2017) - Saxena, Anita; Desai, Ankush; Narvencar, Kedareshwar; Ramakrishnan, Sivasubramanian; Thangjam, Rajendra Singh; Kulkarni, Snehal; Jacques' e Costa, Ana Karina; Mani, Kalaivani; Dias, Amit; Sukharamwala, Ritesh
Abstract: Objectives: Rheumatic heart disease (RHD) continues to be major public health burden in developing world. Echocardiographic screening in school children has shown that subclinical RHD cases are several times more than clinical cases. Recent reports have used World Heart Federation (WHF) criteria. Objective of present study was to determine RHD prevalence using WHF criteria in Indian children. Methods: Children (5–15 years) from randomly selected schools across four sites were included. After focused clinical evaluation, echocardiography was performed using WHF criteria in all children. Images/loops of abnormal cases were analyzed independently by an additional experienced cardiologist. Children with murmur and confirmatory echocardiography were categorized 'clinical RHD'; those with abnormal echocardiography alone were labeled 'subclinical RHD'. Results: Among 16, 294 children included, mean age was 10.8 ± 2.9 years; 55.1% were males; 11, 405 (70%) were from rural areas and 3978 (24.4%) were from government schools. We detected RHD by echocardiography in 125 children [prevalence: 7.7/1000 (95% CI 6.3, 9.0)]. Borderline RHD was present in 93 children (5.7/1000, 95% CI 4.6, 6.9), definite RHD in 32 (2/1000, 95% CI 1.2, 2.6), and clinical RHD in six [0.36/1000, 95% CI: 0.1–0.7]. On univariate analysis, older age, female gender, and higher waist circumference were associated while on multivariate analysis, older age (OR 1.18, 95% CI: 1.09, 1.26) and female gender (OR 1.61, 95% CI: 1.13, 2.3) were associated with RHD. Conclusion: RHD prevalence varies in different parts of India. Echocardiographic prevalence is several times higher than clinical and underscores importance of echocardiographic screening in community.